Reevaluating Tax Debt Collection in Indonesia: A Policy and Legal Framework Analysis - Muhammad Fandy Zainuddin; Afira Nida 'Ulayya; Riska Oktiani (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2026)
Despite certain parameters, tax collection in Indonesia remains suboptimal and a persistent issue. A plethora of existing provisions on tax debt collection in Indonesian tax law present both challenges and opportunities for refinement, spanning laws, ministerial regulations, and circular letters. The method employed in this study is qualitative research. This paper dissects the tax debt collection regulations into three distinct aspects: the statute of limitations for debt collection, enforcement actions, and tax debt write-offs. Using qualitative methods, including policy analysis and in-depth interviews with experts, this paper identifies regulatory gaps and proposes improvements aligned with relevant international best practices. Policy recommendations are derived from in-depth expert interviews, regulatory benchmarks, the Supreme Audit Agency’s recurrent audit findings, international organization’s studies, and government administration principles. To the best of our knowledge, after an extensive literature review, there’s little to no other research that has discussed the topics we’ve studied in this paper; therefore, our research potentially represents the first of its kind in this domain, setting the stage for further research in this field.